The kinematical analysis of 110m hurdles - Shibayama, K.; Fujii, N.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: The purpose of this study was to kinematically analyse 110m hurdlers' motion, with reference to body height.